2022
DOI: 10.1152/ajpcell.00248.2022
|View full text |Cite
|
Sign up to set email alerts
|

The circadian system in cystic fibrosis mice is regulated by histone deacetylase 6

Abstract: Disordered sleep experienced by people with cystic fibrosis (CF) suggest a possible disruption in circadian regulation being associated with the loss of cystic fibrosis transmembrane conductance regulator (Cftr) function. To test this hypothesis, circadian regulation was assessed in a F508del/F508del CF mouse model. CF mice exhibited significant alterations in both timing of locomotor activity and in mean activity per hour in both light-dark (LD) and dark-dark (DD) photoperiods compared to wild type (WT) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…To determine if the Tppp/HDAC6 pathway could be responsible for CF-related airway inflammation, we examined Tppp − / − mice. We have previously shown that Tppp − / − MNE cells have WT levels of CFTR function so we can conclude that any CF-like phenotypes in these mice are not due to a secondary impact on CFTR activity 21 .…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…To determine if the Tppp/HDAC6 pathway could be responsible for CF-related airway inflammation, we examined Tppp − / − mice. We have previously shown that Tppp − / − MNE cells have WT levels of CFTR function so we can conclude that any CF-like phenotypes in these mice are not due to a secondary impact on CFTR activity 21 .…”
Section: Discussionmentioning
confidence: 66%
“…This hypothesis stems from previous observations that Hdac6 depletion from CF mice normalized responses to this challenge suggesting a microtubule-related mechanism 5 . We have also recently demonstrated that Tppp − / − mice effectively replicate another phenotype of CF mice, circadian timing dysregulation 21 , 28 . To determine if the Tppp/HDAC6 pathway could be responsible for CF-related airway inflammation, we examined Tppp − / − mice.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations